Pengembangan lkm berbasis inquiry untuk mengoptimalkan kemampuan penalaran adaptif - Yenni Yenni; Eka Rachma Kurniasi (Department of Mathematics Education, UIN Sunan Gunung Djati Bandung, West Java, Indonesia, 2018)
Kemampuan penalaran adaptif adalah salah satu unsur penting dalam menunjang keberhasilan mahasiswa untuk mencapai hasil belajar maksimal pada mata kuliah teori bilangan. Unsur ini berperan untuk meningkatkan kemampuan mahasiswa dalam memberikan alasan atau bukti terhadap kebenaran suatu pernyataan, menarik kesimpulan dari suatu pernyataan dan memeriksa kesahihan suatu argument. Agar dapat mengoptimalkan kemampuan ini, peneliti menyusun lembar kerja mahasiswa(LKM) berbasis Inquiry. LKM yang dilengkapi dengan langkah langkah Inquiry membuat mahasiswa aktiv berlatih mengikuti perintah dan urutan yang tertera pada LKM. Dengan sering berlatih mengisi LKM dan kewajiban mengkomunikasin hasil, kemampuan adaptif mahasiswa dapat terlatih dan pada akhirnya membantu mahasiswa meraih hasil maksimal pada belajar teori bilanganDevelopment of inquiry-based student worksheets to optimize adaptive reasoning abilitiesThe aim of this study is to produce Student Worksheets that can optimizing the ability of adaptive reasoning. The method used is development research. Adaptive reasoning ability is the focus of research because it is one of the important elements in supporting students' success in achieving maximum learning outcomes in number theory courses. This element has a role to improve the ability of students to provide reasons or evidence of the truth of a statement, draw conclusions from a statement and examine the validity of an argument. In order to optimizing this ability, researchers compiled Inquiry-based student worksheets. Student worksheet that are equipped with Inquiry steps make active students practice following the orders and sequences listed on the student worksheet. By often practicing questions that are indicators of adaptive reasoning, filling in student worksheets and the obligation to communicate results, adaptive abilities of students can be trained and ultimately help students achieve maximum results in learning number theory. Thus, number theory student worksheets compiled with inquiry are effective in optimizing adaptive reasoning abilities